Design and optimization of a three degrees-of-freedom spatial motion compliant parallel mechanism with fully decoupled motion characteristics - Pham, Minh Tuan (2020)
This paper presents a novel three degrees-of-freedom (DOF) compliant parallel mechanism (CPM) with a fully decoupled spatial motion (θX-θY-Z) and optimized mechanical properties. To design the CPM using the beam-based structural optimization method, several novel criteria for synthesizing three-legged CPMs with fully decoupled motions are derived. The obtained results suggest that the synthesized CPM delivers a diagonal compliance matrix, a large workspace of 10deg×10deg×7mm, fast dynamic response of ?100Hz, and good stiffness performance whereby the translational and rotational stiffness ratios are ?3600 and ?570, respectively. A prototype of the synthesized CPM is fabricated using one of the three-dimensional (3D) printing technologies, electron beam melting (EBM). Experimental results have shown that the 3D printed CPM can produce the full workspace with deterministic mechanical properties whereby the highest deviations between the theoretical and experimental results are 11.2% and 1% for stiffness and dynamic behaviors, respectively. Importantly, the decoupled-motion characteristic is also verified via an energy approach, i.e., the energies of the undesired parasitic motions are minor (<1%) as compared with the energy of the desired motion. In addition, several comparisons are conducted to clarify the advantages of the synthesized CPM to the existing designs. All these investigations suggest that the proposed CPM can be used in precision positioning systems due to the good stiffness characteristics, large workspace, fast dynamic response, and decoupled output motions.